2019
DOI: 10.1088/1755-1315/395/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

Vertical vegetable growing: creating tomato varieties for multi-tiered hydroponic installations

Abstract: The relevance of vertical vegetable growing is due to the need to ensure an uninterrupted supply of food and reduce the cost of food production in terms of moving the majority of the population of the Earth into urban space. The market of vertical vegetable growing can be characterized as capacious and fast-growing. In the Russian Federation, this market is still developing. The main vegetable crops are not represented in it. The purpose of the study was to create tomato varieties for the vertical vegetable gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This may be achieved by the use of automated techniques and through the application of nutrient and water sensors in a soil cultural system or in hydroponics, aeroponics, or aquaponics soilless system [343,344]. Moreover, a selection of new "short-stature" tomato cultivars adapted for the growth in a multi-tiered, narrow-rack, indoor conditions [345] or the creation of small tomatoes suitable for vertical farming using the CRISPR-Cas technology are new inputs that may satisfy the requirements of advanced and sustainable tomato cultivation. Since tomato plants grow mostly outdoors in the Mediterranean region (e.g., open field vs. protected cultivation 5.7/0.5 million tonnes in Italy, 3.3/1.6 million tonnes in Spain) [342], the main impact of climate change on tomato is still to be considered directly in open field.…”
Section: Effect Of Climate Change On Tomato Diseasesmentioning
confidence: 99%
“…This may be achieved by the use of automated techniques and through the application of nutrient and water sensors in a soil cultural system or in hydroponics, aeroponics, or aquaponics soilless system [343,344]. Moreover, a selection of new "short-stature" tomato cultivars adapted for the growth in a multi-tiered, narrow-rack, indoor conditions [345] or the creation of small tomatoes suitable for vertical farming using the CRISPR-Cas technology are new inputs that may satisfy the requirements of advanced and sustainable tomato cultivation. Since tomato plants grow mostly outdoors in the Mediterranean region (e.g., open field vs. protected cultivation 5.7/0.5 million tonnes in Italy, 3.3/1.6 million tonnes in Spain) [342], the main impact of climate change on tomato is still to be considered directly in open field.…”
Section: Effect Of Climate Change On Tomato Diseasesmentioning
confidence: 99%
“…The commonly cultivated vegetables under the hydroponic system include spinach, lettuce, and kale, which grow well in hydroponic culture owing to their shallow root systems and quick growth cycle (Jones, 2014). Moreover, tomatoes (Balashova et al, 2019), cucumbers, peppers, and strawberries also can be grown effectively in hydroponic culture (Jones, 2014). Vegetable production through a hydroponic system depends on delivering the essential nutrients to roots directly via nutrient solution.…”
Section: Selection Suitability and Applications Of Hydroponics For Ve...mentioning
confidence: 99%
“…Compared to conventional tomato cultivation, evaluating the economic effectiveness of multi-tiered narrow-rack hydroponics showed inherent advantages (Balashova et al 2019). Askari-Khorasgani and Pessarakli (2020a) observed that in the vermin hydroponic system, the most important thing is in the vermiponic units, the most effective tomato (S. lycopersicum) cultural customs provide the best economical and environmentally friendly method of horticultural crops.…”
Section: Tomato Productionmentioning
confidence: 99%